WORKING OUT OF THE STAND FOR RESEARCH OF HYDRODYNAMIC EFFECTS IN FLOWING PART OF THE RDAH - Овчаренко, Михайло Сергійович (Eastern-European Journal of Enterprise Technologies, 2012)
We describe the existing rotary homogenizer. The expediency of using rotor-dynamic machine homogenizer (RDAH) for the process with high demands on the product fineness is justified.